QTL mapping for root traits during post-tillering stage under moisture-deficit stress in wheat - Sreehari V. Santhosh; Sukumar Taria; Sudhir Kumar; Hari Krishna; Karthik Kumar Manjunath; Seetha Laxmi; Arumugam Tamilselvan; Raman Rajasekar; Ezhumalai Sivapragasam; Allimuthu Elangovan; Biswabiplab Singh; Dhandapani Raju; et al. (Plant Molecular Biology, 2026)

Repurposing banana sheath scutcher for soil conservation: Improving soil water holding capacity and nutrient availability - Prabhu Govindasamy; N. Celcia Jenifer; K. Sedhupathi; K.J. Jeyabaskaran; Pramod Shelake; I. Ravi; M. Loganathan; V. Sukumar; R. Selvarajan (Bioresource Technology Reports, 2026)

Correction: Molecular characterization of Indian contagious ecthyma (Orf) virus isolates by A32L gene and its encoded ATPase protein - Sowmiya P. V.; Ramya Kalaivanan; Sukumar Kuppannan; Madheswaran Rajamanickam; Ponnusamy Periyasamy; Selvaraju Mani (Tropical Animal Health and Production, 2026)

Molecular characterization of Indian contagious ecthyma (Orf) virus isolates by A32L gene and its encoded ATPase protein - Sowmiya P. V.; Ramya Kalaivanan; Sukumar Kuppannan; Madheswaran Rajamanickam; Ponnusamy Periyasamy; Selvaraju Mani (Tropical Animal Health and Production, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Investigation of Natural Extracts and Sodium Bisulfite Impact on Thermal Signals and Physicochemical Compositions of Litopenaeus vannamei during Chilled Storage - Udayasoorian Lalithapriya; Peter Mariajenita; V. Renuka; Kasirajan Sudharsan; S. Karthikeyan; Meenakshisundaram Sivarajan; D. Murugan; Muthusamy Sukumar (Journal of Aquatic Food Product Technology, 2019)

Bdnf mRNA splice variants differentially impact CA1 and CA3 dendrite complexity and spine morphology in the hippocampus - Kristen R. Maynard; John W. Hobbs; Mahima Sukumar; Alisha S. Kardian; Dennisse V. Jimenez; Robert J. Schloesser; Keri Martinowich (Brain Structure and Function, 2017)

Removal of Cr(VI) using co-immobilized activated carbon and Bacillus subtilis: fixed-bed column study - C. Sukumar; V. Janaki; K. Vijayaraghavan; S. Kamala-Kannan; K. Shanthi (Clean Technologies and Environmental Policy, 2017)

Molecular Epidemiology of Nontyphoidal Salmonella in Poultry and Poultry Products in India: Implications for Human Health - Sellappan Saravanan; Venketaraman Purushothaman; Thippichettypalayam Ramasamy Gopala Murthy; Kuppannan Sukumar; Palani Srinivasan; Vasudevan Gowthaman; Mohan Balusamy; Robert Atterbury; Suresh V. Kuchipudi (Indian Journal of Microbiology, 2015)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Biosorption of chromium(VI) using Bacillus subtilis SS-1 isolated from soil samples of electroplating industry - C. Sukumar; V. Janaki; Seralathan Kamala-Kannan; K. Shanthi (Clean Technologies and Environmental Policy, 2014)

Removal of chromium using Rhizobium leguminosarum - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2012)

Rapid detection of Salmonella enterica serovars by multiplex PCR - G. Jeyasekaran; K. Thirumalai Raj; R. Jeya Shakila; A. Jemila Thangarani; D. Sukumar; V. Abdul Kadhar Jailani (World Journal of Microbiology and Biotechnology, 2011)

Implications of climate change on mitigation potential estimates for forest sector in India - N. H. Ravindranath; Rajiv K. Chaturvedi; N. V. Joshi; R. Sukumar; Jayant Sathaye (Mitigation and Adaptation Strategies for Global Change, 2011)

Impact of climate change on Indian forests: a dynamic vegetation modeling approach - Rajiv K. Chaturvedi; Ranjith Gopalakrishnan; Mathangi Jayaraman; Govindasamy Bala; N. V. Joshi; Raman Sukumar; N. H. Ravindranath (Mitigation and Adaptation Strategies for Global Change, 2011)

Optimisation of extracellular tannase production from Paecilomyces variotii - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2010)

Patterns of tree growth in relation to environmental variability in the tropical dry deciduous forest at Mudumalai, southern India - Cheryl D. Nath; H. S. Dattaraja; H. S. Suresh; N. V. Joshi; R. Sukumar (Journal of Biosciences, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Simple sequence repeats as useful resources to study transcribed genes of cotton - Sukumar Saha; Mehmet Karaca; Johnie N. Jenkins; Allan E. Zipf; O. Umesh K. Reddy; Ramesh V. Kantety (Euphytica, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)